Biochemical and electrophoretic evaluation of clinically suspected multiple myeloma - DR SREEVANI NAMANI,; DR LAXMI NARAYANA SRIPURAM, (International Journal of Pharma and Bio Sciences, 2017)
Multiple Myeloma (MM) is a malignant plasma cell disorder that accounts for approximately 10% of all hematologic cancers, typically occurring in elderly patients. A study was conducted on 25 (n=25) subjects clinically suspected multiple myeloma cases considered as study group and 25 (n=25) healthy volunteer individuals taken as control group. The biochemical parameters such as serum total protein, serum albumin, serum calcium and serum creatinine levels in both study and normal healthy subjects were evaluated that may be useful in the diagnosis of the disease. Mean and SD values of serum total proteins, serum creatinine and serum calcium were significantly high in study cases compared to control group and are statistically significant (p < 0.05, 0.001). Whereas, serum albumin levels showed slight decrease and are not statistically significant (p > 0.05). Present study showed abnormal eletrophoretic pattern in multiple myeloma cases, with M band identified in the gamma region. Increased serum total protein indicates the increased paraprotein production. Increased serum calcium and serum creatinine levels in the study group indicate bone resorption and renal damage respectively. The nature of complex interpretations have yet to be elucidated and improving our understanding of these interpretations may provide us with new opportunities to identify novel therapeutic approaches to treating both the bone destruction and the myeloma disease itself.